Difficulties that Arise in the Process of Literary Translation and Their Functions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Scientists and researchers of translation studies have been studying the problem of translating artistic texts for many centuries. In this article, the author discusses the concept of literary translation, its features, difficulties faced by translators, as well as the main approaches to this type of translation activity. The increasing number of works of art and the need to translate them into foreign languages ​​confirm the relevance of this article.